Halal Compliance impact on Organizational Performance: the role of religiosity - Baharuddin, Sitti Aminah; Mohamed Ismail, Risyawati (International Journal of Supply Chain Management, 2018)
The purpose of this paper is to study how the implementation of Halal certification could facilitate successful certification implementation in halal manufacturing company in Malaysia. The paper is based on a thorough review of published journals on the subject of implementation of halal level compliance and performance that moderate by religiosity. In recent years, 70 percent of the Malaysian halal manufacturer being non-Muslim. Thus, it is important to study the hindsight of the halal manufacturer on regard the compliance and performance, since there are lack of study examine the impact if religiosity in the area of operation organizational performance.